Perception of Basic Level Teachers’ on Critical Thinking (CT) Strategies - Acharya, Nara Hari (Innovative Research Journal, 2024)
The perception of basic level teachers in mathematics is a qualitative study. 5 basic level teachers were chosen purposively who had participated in 5 days CT training. The basic level teachers’ perceived critical thinking (CT) as a sequential process of developing cognitive skills and problem solving among the students. The teaching CT to their students provides the intellectual stimuli that will facilitate thinking alternative way in mathematics with increasing the ability of explaining the ideas and concepts in their own words linking with context. Although the students in classroom present their ideas and in pairs and in groups with logical thinking and solve problems using new approaches are less demonstrated in assessment. The materials presented developed the cognitive skills to gain understanding and assimilate the ideas.